2020
DOI: 10.1001/jamanetworkopen.2020.0100
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Folate Levels With Cardiovascular Mortality Among Adults With Rheumatoid Arthritis

Abstract: IMPORTANCE Patients with rheumatoid arthritis (RA) are at high risk for cardiovascular (CV) mortality, attributed to chronic inflammation coupled with elevated circulatory homocysteine levels. Increasing the serum folate level reduces homocysteine, but the association of serum folate concentration with CV mortality in patients with RA has not been previously examined. OBJECTIVE To examine the association of serum folate concentration and CV mortality risk among patients with RA. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Among participants with rheumatoid arthritis in NHANES III (1988)(1989)(1990)(1991)(1992)(1993)(1994) and 2011, circulating folate levels were inversely associated with risk of all-cause mortality and CVD mortality, 25 whereas a U-shaped association between serum folate level and CVD mortality was observed among adults with hypertension. 26 However, among adults with T2D, the evidence regarding folate status and long-term health outcomes is limited and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Among participants with rheumatoid arthritis in NHANES III (1988)(1989)(1990)(1991)(1992)(1993)(1994) and 2011, circulating folate levels were inversely associated with risk of all-cause mortality and CVD mortality, 25 whereas a U-shaped association between serum folate level and CVD mortality was observed among adults with hypertension. 26 However, among adults with T2D, the evidence regarding folate status and long-term health outcomes is limited and mixed.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence on the association of folate with the all-cause mortality rate in the general population remains controversial. Several studies have demonstrated that folate supplementation could reduce the risk of CVD-related death, which might be attributable to serum homocysteine reduction (137). In contrast, Ebbing et al reported that folate treatment was associated with increased risks of cancer outcomes and allcause mortality in patients with ischemic heart disease (138).…”
Section: Discussionmentioning
confidence: 99%
“…Although the associations between folate levels and mortality have been previously investigated, the current evidence is not yet conclusive: some studies did not find any significant associations (18,19); among studies that did, J-or U-shaped associations (20)(21)(22)(23), positive linear associations (24), and inverse associations (17,25,26) have all been reported; additionally, two studies found that only low folate levels were significantly associated with increased risk of mortality (27,28). However, most of the previous studies used serum folate as the main exposure, and only two studies used RBC folate in the analysis (21,24).…”
Section: Discussionmentioning
confidence: 57%
“…The leading cause of death falls into 9 cause-specific death categories based on the International Classification of Diseases, 10th Revision (ICD-10) code on the participant's death certificate (16). We defined all-cause mortality as death because of any reason, while cardiovascular mortality included deaths reportedly due to disease of the heart (leading death code 001) or cerebrovascular diseases (leading death code 005) (17).…”
Section: Ascertainment Of Mortality Outcomesmentioning
confidence: 99%